2021
DOI: 10.3390/en14206772
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Durability and Grindability of Pellets after Torrefaction Process

Abstract: Renewable energy sources and their part in the global energy mix are beneficial to energy diversification and environment protection. However, raw biomass is characterized by low heating value, hydrophilic properties, various mechanical durability, and the logistic challenges related to transportation and storage. One frequently used process of combined biomass valorization is torrefaction and pelletization, which increase the heating value, homogeneity, and hydrophobicity of the fuel. However, industrial clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Torrefaction is a common pre-production technique that directly affects the quality of the pellets. Despite its benefits in improving pellet density by reducing the moisture content, enhancing the grinding properties, and altering the chemical compositions [144], it has been observed that torrefied materials have diminished durability properties [136,138,163]. This finding is supported by the analyzed data, as demonstrated by the significantly lower mechanical durability values in torrefied wheat straw pellets compared to non-torrefied pellets (Table 3).…”
Section: Mechanical Durabilitymentioning
confidence: 81%
“…Torrefaction is a common pre-production technique that directly affects the quality of the pellets. Despite its benefits in improving pellet density by reducing the moisture content, enhancing the grinding properties, and altering the chemical compositions [144], it has been observed that torrefied materials have diminished durability properties [136,138,163]. This finding is supported by the analyzed data, as demonstrated by the significantly lower mechanical durability values in torrefied wheat straw pellets compared to non-torrefied pellets (Table 3).…”
Section: Mechanical Durabilitymentioning
confidence: 81%
“…Arias et al [13] reported that the torrefaction of eucalyptus biomass at 240 • C with a 30-min residence time had a substantial effect on the chemical and grindability properties. Furthermore, Dyjakon and Noszczyk [14] evaluated the effect of the torrefaction temperature on the mechanical durability of pellets made from various biomass wastes and on the required energy for grinding.…”
Section: Introductionmentioning
confidence: 99%